Characteristics and outcomes of patients with double refractory and double exposed chronic lymphocytic leukemia - James T. Yoon; Yinglu Zhou; Mariia Mikhaleva; Daniel S. Choi; Stacey M. Fernandes; Philippe Armand; Amy C. Bessnow; Jennifer L. Crombie; David C. Fisher; Eric D. Jacobsen; Caron A. Jacobson; Austin I. Kim; et al. (Blood Advances)
Abstract: We analyzed the characteristics and outcomes of 95 patients with chronic lymphocytic leukemia (CLL) after Bruton tyrosine kinase inhibitor (BTKi) and B-cell lymphoma 2 inhibitor (BCL2i) failure. To clearly distinguish sensitivity and resistance to the targeted treatment classes, we defined double refractory (DR) CLL when progressive disease occurred during active treatment with a BTKi and a BCL2i, given sequentially or in combination, and double exposed (DE) disease when treatment with either or both of these agents was discontinued due to reasons other than progression. Thirty patients (31.6%) had DR CLL, and 65 (63.2%) had DE CLL. The DR group more frequently had unmutated immunoglobulin gene heavy chain variable (97%), TP53 aberration (73%), and BTK mutations (59%) than the DE group (75%, 46%, and 27%, respectively). The median number of total lines of therapy was 6 for DR and 3 for DE. Nearly all DR patients (97%) required subsequent therapy after developing DR CLL. The most commonly used treatment was noncovalent BTKis (34%), followed by concurrent covalent BTKi and BCL2i (28%) and CD19 chimeric antigen receptor-modified T cells (24%). Treatment for DE CLL was less frequently observed (26%). The median overall survival (OS) was 2.2 years once DR developed, despite the frequent initial responses to noncovalent BTKis or cellular therapy in the cohort. Patients with DE CLL demonstrated favorable survival (median OS not reached) and durable response to subsequent therapy.